2015
DOI: 10.1182/blood.v126.23.126.126
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Factor Xa Variants Retain Procoagulant Activity Independent of Direct Factor Xa-Inhibitors

Abstract: The venom of the Australian Elapid snake Pseudonaja textilis contains a prothrombin-activating complex that consists of factor Xa (FXa) and factor Va (FVa) homologs which are evolutionary adapted to derail the hemostatic system of its prey, leading to runaway coagulation. These adaptations include functional resistance to inactivation by the main inhibitors of coagulation, antithrombin and activated protein C. Further studies revealed that venom FXa, unlike other FXa species, is also resistant to inhibition by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, lacking of agents to reverse its anticoagulation effect remains a major concern for clinical application of RIV. In exploration of RIV rescuing agents, Verhoef et al (2017) found that the F174A mutant of FXa was resistant to the RIV-like inhibitor, Apixaban, while retaining the catalytic activity, and suggested local modifications on S4 pocket may reduce the binding affinity of the direct inhibitor to FXa. However, Verhoef's computational simulations mainly focused on the mobility of the 99 loop in wild-type and P. textilis isoform FXa, and did not elaborate the molecular mechanism of the F174A mutant in detail.…”
mentioning
confidence: 99%
“…However, lacking of agents to reverse its anticoagulation effect remains a major concern for clinical application of RIV. In exploration of RIV rescuing agents, Verhoef et al (2017) found that the F174A mutant of FXa was resistant to the RIV-like inhibitor, Apixaban, while retaining the catalytic activity, and suggested local modifications on S4 pocket may reduce the binding affinity of the direct inhibitor to FXa. However, Verhoef's computational simulations mainly focused on the mobility of the 99 loop in wild-type and P. textilis isoform FXa, and did not elaborate the molecular mechanism of the F174A mutant in detail.…”
mentioning
confidence: 99%